2015
DOI: 10.1007/s00382-015-2720-0
|View full text |Cite
|
Sign up to set email alerts
|

What drives LGM precipitation over the western Mediterranean? A study focused on the Iberian Peninsula and northern Morocco

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 83 publications
4
45
0
Order By: Relevance
“…The maximum of the corresponding parabola yields a better approximation of the exact latitude of the maximum jet wind. This method allows for a more accurate finding of the latitude of the jet maximum (Chavaillaz et al, 2013;Beghin et al, 2015). We find a good linear correlation between the shift of the North Atlantic jet and the Scandinavian precipitation anomaly during the winter season (Fig.…”
Section: Precipitation Changes Over Scandinavia: Implication Of the Jmentioning
confidence: 56%
See 2 more Smart Citations
“…The maximum of the corresponding parabola yields a better approximation of the exact latitude of the maximum jet wind. This method allows for a more accurate finding of the latitude of the jet maximum (Chavaillaz et al, 2013;Beghin et al, 2015). We find a good linear correlation between the shift of the North Atlantic jet and the Scandinavian precipitation anomaly during the winter season (Fig.…”
Section: Precipitation Changes Over Scandinavia: Implication Of the Jmentioning
confidence: 56%
“…Using the PMIP3 model outputs for the LGM and the PI time slices, Beghin et al (2015) found a correlation between the southward shift of the North Atlantic jet stream from the preindustrial to the LGM periods and the winter precipitation changes over the Iberian Peninsula. Following the same approach, we examine whether a similar mechanism to the one found in (Beghin et al, 2015) may explain the precipitation changes over Scandinavia when the LIS characteristics (albedo and topography) are modified. Similarly to Chavaillaz et al (2013), we use the 850 hPa zonal wind to define the jet stream.…”
Section: Precipitation Changes Over Scandinavia: Implication Of the Jmentioning
confidence: 98%
See 1 more Smart Citation
“…Storm tracks, jet stream, and Intertropical Convergence Zone (ITCZ) meridional shifts may also be linked to sea surface temperature/surface air temperature changes in the North Atlantic (e.g. Beghin et al, ; Brayshaw et al, ; Park et al, ), but evidence for this mechanism in our simulations is inconclusive. A set of specific sensitivity studies using a hierarchy of models (including higher spatial resolution and idealized simulations) would be needed, in order to analyze quantitatively the potential mechanism linking both monsoons and storm track dynamics on precessional time scales.…”
Section: Implications For the Interpretation Of The Sedimentary Recordmentioning
confidence: 74%
“…If the westerlies had shifted south (north), this may have led to a reduction (an increase) in eastward sea ice transport to the region of NADW formation, and thus modify the strength (or perhaps the sign) of the sea ice process. Since the meridional shift of the westerlies in response to glacial ice sheets depends on the model (Laîné et al 2009;Rivière et al 2010;Hofer et al 2012;Merz et al 2015;Beghin et al 2015) and the configuration of the ice sheets (Kageyama et al 1999, Li andBattisiti 2008;Laîné et al 2009;Beghin et al 2015), the effect of the sea ice process related to the meridional shift of the westerlies should also depend largely on individual simulations. More studies are required to understand the precise role of the sea ice process related to the meridional shift of the westerlies.…”
Section: Discussionmentioning
confidence: 99%